Study of Sulphate Origin in Shallow Groundwater in the Vicinity of Bantar Gebang-Bekasi Landfill Using Sulphur-34 and Oxygen-18 - E.R. Pujiindiyati; Syafalni Syafalni (PPIKSN-BATAN, 2007)
Bantar Gebang-Bekasi landfill-West Java has caused a social impact due to the possibility of groundwater contamination. An investigation to trace sulphate origin in shallow groundwater in surrounding of Bantar Gebang -Bekasi landfill had been done. The methods were related to Rafter for extraction of CO2 and Robinson-Kusakabe for extraction of SO2 gas. Both gases were injected to mass spectrometer for measuring of δ 18O (SO42-) and δ 34S (SO42-). The results showed that a mixing of sulphate from leachate water to shallow groundwater had occurred. The more enriched value of δ 34S (SO42-) as much as 8.87 o/oo in leachate water compared to shallow groundwater having that value of 3.92o/oo to 6.66 o/oo might be caused by rapidly growth of sulphate reducing bacteria. The source of oxygen in sulphide oxidation dominantly came from atmosphere whereas percentage of H2O supplying oxygen was 0-25% for groundwater and 40% for leachate water. The extend of this value in leachate water might be caused by higher degree of bacteria, higher content of heavy metals and lower content of dissolved atmospheric oxygen.